2008
DOI: 10.1016/j.ejcts.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Heart transplantation in patients with liver cirrhosis

Abstract: Although there was high mortality and morbidity, patients with end-stage heart failure and liver cirrhosis can be considered for heart transplantation with careful case selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 24 publications
1
34
0
1
Order By: Relevance
“…Our data add to the existing evidence in the literature that patients with cardiac hepatopathy may, if carefully selected after considering additional clinical and laboratory parameters, be appropriate candidates for cardiac transplantation. 8,11,13,14 Our findings are in agreement with studies that have shown that after successful cardiac transplantation, patients may show improvement of liver disease in terms of both laboratory values and histologic findings. 11,13,14 Our patients all showed marked improvement in liver enzymes and bilirubin levels at 6 months and further improvement at 1 year post-transplant with normal levels observed in most patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data add to the existing evidence in the literature that patients with cardiac hepatopathy may, if carefully selected after considering additional clinical and laboratory parameters, be appropriate candidates for cardiac transplantation. 8,11,13,14 Our findings are in agreement with studies that have shown that after successful cardiac transplantation, patients may show improvement of liver disease in terms of both laboratory values and histologic findings. 11,13,14 Our patients all showed marked improvement in liver enzymes and bilirubin levels at 6 months and further improvement at 1 year post-transplant with normal levels observed in most patients.…”
Section: Discussionsupporting
confidence: 92%
“…The risk of perioperative death is markedly increased by cirrhosis due to any cause, [3][4][5] and cirrhosis is also associated with increased post-operative complications following cardiac surgery, [6][7][8][9] including increased rates of sepsis and bleeding. Serum bilirubin has been found to correlate with operative mortality and with the presence of cardiac cirrhosis in patients with primary pulmonary hypertension undergoing heartlung transplantation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a post reperfusion injury, secondary coagulopathy, and post-operative hydrostatic pulmonary edema may worsen the clinical outcome [95]. In addition, cirrhotic patients with concomitant severe cardiomyopathy may benefit from cardiac transplantation [96]. receptor agonists are responsible for hydrogen sulfide production; moreover, NCX-1000 may release NO in the liver [97].…”
Section: Liver Transplantationmentioning
confidence: 99%